2004
DOI: 10.1007/s00705-004-0369-9
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of avian infectious bronchitis virus strains isolated in Japan

Abstract: To define the origin and evolution of recent avian infectious bronchitis virus (IBV) in Japan, a genetic analysis was performed. By phylogenetic analysis based on the S1 gene including the sequence of the hypervariable regions, IBV isolates in Japan were classified into five genetic groups, which included two already-known groups (Mass and Gray). Among them, three major genetic groups were associated with the recent outbreaks of IB in Japan. One group is indigenous to Japan and could not be placed within the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
87
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 26 publications
1
87
0
Order By: Relevance
“…Of these, the S1 glycoprotein is associated with virus attachment and is a major target of the neutralizing antibodies in chickens [5,8], so serotypic evolution in IBV is associated primarily with the sequences of the S1 glycoprotein [10,18]. Therefore, recent genetic grouping of IBV has been performed mainly on the basis of the nucleotide sequences of the S1 glycoprotein gene [9,11,12,17,18,20].Previously, our phylogenetic analysis of mainly hypervariable (HVR) regions of S1 glycoprotein genes revealed that Japanese IBV strains could be classified into five genetic groups, one of which is indigenous to Japan and can not be placed within the existing groups in other countries [14].In the present report, to define the epidemiology or relationships among recent IBV isolates in Japan during 2003-2007, we used essentially the same procedure in an attempt to characterize eight Japanese IBV isolates from chickens.The IBV isolates were obtained from prefecture-based regional animal hygiene service centers in Japan (Table 1). Most of the IBV specimens were isolated by two or three passages using 10-day-old embryonated chicken eggs.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, the S1 glycoprotein is associated with virus attachment and is a major target of the neutralizing antibodies in chickens [5,8], so serotypic evolution in IBV is associated primarily with the sequences of the S1 glycoprotein [10,18]. Therefore, recent genetic grouping of IBV has been performed mainly on the basis of the nucleotide sequences of the S1 glycoprotein gene [9,11,12,17,18,20].Previously, our phylogenetic analysis of mainly hypervariable (HVR) regions of S1 glycoprotein genes revealed that Japanese IBV strains could be classified into five genetic groups, one of which is indigenous to Japan and can not be placed within the existing groups in other countries [14].In the present report, to define the epidemiology or relationships among recent IBV isolates in Japan during 2003-2007, we used essentially the same procedure in an attempt to characterize eight Japanese IBV isolates from chickens.The IBV isolates were obtained from prefecture-based regional animal hygiene service centers in Japan (Table 1). Most of the IBV specimens were isolated by two or three passages using 10-day-old embryonated chicken eggs.…”
mentioning
confidence: 99%
“…Viral RNA was extracted from infected allantoic fluids using an ISOGEN-LS kit (Nippon Gene, Tokyo, Japan). Reverse transcription, PCR amplification, sequencing and phylogenetic analysis were performed as described previously [14].The expected sizes of DNA fragments were successfully amplified by RT-PCR from all the IBV samples in this study. Determination of the nucleotide sequences of the obtained PCR products revealed the diversity in their lengths (677-692 bp).…”
mentioning
confidence: 99%
See 3 more Smart Citations